Characterization of the texture and flavor profiles of hazelnut puree - Ozcelık, B.; Karaalı, A. (Wiley, 2002)
AbstractFlavor and textural characteristics of three commercially produced hazelnut purees, roasted at 120, 140 and 150C, respectively and ground to different particle sizes were determined using flavor and texture profiling. Instrumental color and texture values and particle sizes were also determined.The texture profile was evaluated by using 14 texture attributes: heaviness, wetness, slipperiness, oiliness, melting, viscosity, spreadability, cohesiveness, adhesiveness, smoothness, grainy, gumminess, mouth coating ability and overall acceptability. The flavor profile was evaluated using 10 flavor attributes: roasted, burnt, rancid, raw hazelnut flavors, sweetness, aroma, strength of taste, tongue sting, aftertaste and overall acceptability.The scores indicate that hazelnut puree is a viscous and heavy product with high adhesiveness and mouth‐coating ability but is not significantly cohesive. Its taste and aroma were characterized by roasted and raw hazelnut flavors, significant tongue sting and an aftertaste.